2021
DOI: 10.3168/jds.2020-20010
|View full text |Cite
|
Sign up to set email alerts
|

Associations between feed efficiency and aspects of lactation curves in primiparous Holstein dairy cattle

Abstract: Genetic selection for improved feed efficiency in dairy cattle has received renewed attention over the last decade to address the needs of a growing global population. As milk yield is a critical component of feed efficiency metrics in dairy animals, our objective was to evaluate the associations between feed efficiency in primiparous Holstein cattle and parameters of a mathematical model describing individual lactation curves. The Dijkstra lactation curve model was fit to individual lactation records from 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(56 reference statements)
1
4
0
Order By: Relevance
“…Lactation curve parameter estimates, while not statistically different between treatment groups, were similar to those previously reported for both primiparous and multiparous Holstein dairy cattle (Dematawewa et al, 2007, Dijkstra et al, 2010, Seymour et al, 2021a. It is of note, however, that the model evaluated in the present study does not account for changes in milk component yields.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Lactation curve parameter estimates, while not statistically different between treatment groups, were similar to those previously reported for both primiparous and multiparous Holstein dairy cattle (Dematawewa et al, 2007, Dijkstra et al, 2010, Seymour et al, 2021a. It is of note, however, that the model evaluated in the present study does not account for changes in milk component yields.…”
Section: Discussionsupporting
confidence: 86%
“…It is of note, however, that the model evaluated in the present study does not account for changes in milk component yields. The model proposed by Dijkstra et al (1997) has previously been found to poorly fit yields of FCM and ECM in primiparous animals due to the changes in milk component concentrations over time; the high content of fat and protein in early lactation with decreasing concentrations as lactation progresses serves to flatten the ECM and FCM curves of primiparous animals, resulting in issues generating accurate parameter estimates from these curves (Seymour et al, 2021a). The response, or lack thereof, in primiparous animals is currently unclear; as this study was not designed to properly evaluate potential response differences between parity groups, these findings are likely the result of insufficient statistical power due to either the small number of primiparous animals used, responses too small to detect given the variation in the primiparous group, or a combination of these factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same pattern has been observed with methane emissions, where heritability estimates fluctuate throughout the lactation [ 28 ]. In the current study, cows were measured for methane emissions in mid-lactation (120 to 150 DIM) for a period of five consecutive days as part of a larger project that aims to increase feed efficiency after the peak of lactation, i.e., after 60 DIM [ 13 , 42 ]. Additionally, it is worth noting that despite repeated measures having added value, if the tests are separated by longer periods (i.e., days to weeks) their repeatability could be higher compared to shorter term measurements (i.e., minutes to few hours).…”
Section: Resultsmentioning
confidence: 99%